Misi Bagi Pertumbuhan Gereja Melalui Kontekstualisasi Praktik Ibadah Penghiburan Dalam Tradisi Slametan Di Masyarakat Jawa - Lawalata, Mozes (JURNAL LUXNOS, 2024)
Abstract: This article aims to explain the importance of contextualizing the practice of consolation worship in the slametan tradition in Javanese society as one of the church's missions for church growth. Slametan is a Javanese tradition that involves ceremonial offerings of food to ancestors and gods as a form of spiritual honor and respect. In the context of the church, the practice of consolation worship can be an effective means of connecting with the Javanese community and strengthening the relationship between the church and the community. To achieve the objectives and discussion, the researcher used a qualitative method with a descriptive-analytical approach. Data were collected through literature study, direct observation, interviews with church leaders and Javanese community members, as well as content analysis of relevant sources. Data analysis was conducted to identify challenges and opportunities in contextualizing the practice of consolation worship in the slametan tradition. The results show that contextualizing the practice of consolation worship in the slametan tradition can produce a positive impact on church growth, strengthen relationships with Javanese communities, and provide relevant and meaningful pastoral care. Contextualization helps the church to build an inclusive community, where Javanese people feel valued, recognized, and accepted in the context of their faith. This research can also contribute to the importance of contextualizing the practice of consolation worship in the slametan tradition in Javanese society as one of the church's missions for dynamic church growth.